Position‐Controlled Functionalization of Vacancies in Silicon by Single‐Ion Implanted Germanium Atoms. (19th February 2021) - Achilli, Simona; Le, Nguyen H.; Fratesi, Guido; Manini, Nicola; Onida, Giovanni; Turchetti, Marco; Ferrari, Giorgio; Shinada, Takahiro; Tanii, Takashi; Prati, Enrico
Abstract: Special point defects in semiconductors have been envisioned as suitable components for quantum‐information technology. The identification of new deep centers in silicon that can be easily activated and controlled is a main target of the research in the field. Vacancy‐related complexes are suitable to provide deep electronic levels but they are hard to control spatially. With the spirit of investigating solid state devices with intentional vacancy‐related defects at controlled position, the functionalization of silicon vacancies is reported on here by implanting Ge atoms through single‐ion implantation, producing Ge‐vacancy (Ge V ) complexes. The quantum transport through an array of Ge V complexes in a silicon‐based transistor is investigated. By exploiting a model based on an extended Hubbard Hamiltonian derived from ab initio results, anomalous activation energy values of the thermally activated conductance of both quasi‐localized and delocalized many‐body states are obtained, compared to conventional dopants. Such states are identified, forming the upper Hubbard band, as responsible for the experimental sub‐threshold transport across the transistor. The combination of the model with the single‐ion implantation method enables future research for the engineering of Ge V complexes toward the creation of spatially controllable individual defects in silicon for applications in quantum information technology. Abstract : Spatially controlled functionalized vacancies are created in a silicon channel via high‐precision single‐ion implantation. Upon annealing, they form point defects with deep states in the silicon gap operating up to room temperature. Quantum transport through an array of Ge V complexes displays contributions from weakly localized and delocalized states in the upper Hubbard band, characterized by very different activation energy ( E A ).